Smart Policing Initiatives in Rajasthan: Evaluating E-Tools and Technology Adoption - Gadiya, Kartikay (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The evolution of smart policing reflects a paradigm shift in law enforcement strategies, marked by the integration of digital technologies to enhance efficiency, accountability, and citizen engagement. Rajasthan, known for its historical richness and geographical diversity, has been at the forefront of implementing smart policing initiatives through a robust adoption of e-tools and digital platforms. This article critically evaluates the major technology-driven reforms introduced in Rajasthan’s policing system, their effectiveness, challenges faced, and the road ahead. The analysis is drawn from official sources, field reports, and secondary research to assess how digital transformation is redefining the structure and functionality of policing in Rajasthan.